MODELING OF LABOR MARKET DYNAMICS IN BALIKPAPAN USING THE LOGISTIC GROWTH MODEL - Ginoga, Verri; Julianto, Baskoro Tri (Universitas Airlangga, 2025)
Population growth and labor force dynamics become important issues in development planning, especially in the buffer zone of the National Capital City (IKN) such as Balikpapan City. This study aims to model the dynamics of labor market in Balikpapan City using Verhulst logistic growth model approach. The data used includes the number of labor force and non-labor force in the period of 2007 to 2023, obtained from the Central Bureau of Statistics of East Kalimantan Province. The modeling process is conducted independently to ensure analytical clarity between labor force and non-labor force groups to obtain a more accurate projection. The results of the analysis show that the average population of the labor force is 289,631 people with a growth rate of 7.17%, while the non-labor force has an average of 156,643 people with a growth rate of 4.44%. Model validation showed a coefficient of determination (R²) of 0.87 for the labor force and 0.88 for the non-labor force, indicating a good model fit. The difference in growth rate reflects the potential improvement of labor market condition in Balikpapan City. The findings of this study are expected to be a reference for the government and policy makers in formulating strategies for improving the quality of human resources and inclusive and sustainable employment planning in the buffer zone of IKN.